Energetic efficiency and energy requirements during first stage of lactation in crossbred cows - PURANIK, U K; SINGH, V P; NEMA, R K; TIWARI, D P (The Indian Journal of Animal Sciences, 2013)
The comparative performance of 2 genetic groups of cows (8 in each), viz. genetic group 1( JFL, 1/2 J x 1/4HF xÂ 1/4 G) and genetic group 2 ( FJL, 1/2 HF x 1/4 J x 1/4 G). was studied in terms of nutrient utilization and energetic efficiencies for milk production. DCP and TDN intakes/W 0 75 kg were significantly ( P<0.05) higher in JFL animals. Values for milk, FCM, fat percentage, live weight gain and gross energetic efficiency were higher in JFL but maintenance, milk production and body-weight gain were 54 g/W0 75 kg/day. 224 g/kg FCM